FOLK LIKE US: EMOTIONAL MOVEMENT FROM THE SCREEN AND THE PLATFORM IN BRITISH LIFE MODEL LANTERN SLIDE SETS 1880-1910* - Dr Joe KEMBER,Dr Richard CRANGLE (Fonseca, Journal of Communication, 2023)
The turn of the Nineteenth Century was the golden age of the magic lantern, at least in terms of its popularity across the UK, as in much of Europe and the United States. This article argues that one of the chief reasons for its success in this period was that often it both represented and was presented by individuals similar to those in many of its audiences. Focusing on life model lantern slide series/sets, which were also at their most popular during this period,the article draws on two large datasets in order to consider aspects of screen practice associated with the slides themselves and with their conditions of performance